Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2021)
This edition of KIU Journal of Humanities touches on Development Administration, Social Psychology and Literary Studies. The first part of the Journal addresses issues in Development Aministration such as social security and national development, public service delivery, global pandemic and development, administrative law, foreign direct investment and so on. One of the papers in this section argues that social security scheme in Nigeria is falling short as a response to the needs of the poor and suggests, among others, the need to develop an overarching social security scheme to provide clear institutional roles and responsibilities, lay out series of options for social security in the country. This, according to the paper, is based on the fact that strong institutions are needed as back bone for whatever policy the government is considering to implement.   In the second section which centers on Social Psychology, various social factors which have impacts on the society, which may include drug abuse, feeding habit, ethical consideration etc. are examined. One of these papers reveals that there is a great relationship between Substance Abuse and Suicidal Ideation among Youths in Kaduna North, Nigeria. Based on the findings of this study, it is recommended among others; that there should be measures in place to curb this menace due to its adverse effects on our youths and by implication the nation at large. Another paper also examines the concept of epistemic claim to knowledge and the tripartite criteria arising from Platoâ€™s attempt to justify the claim to knowledge in epistemology. The researcher is of the opinion that there are no absolute criteria that are holistic enough to address the question of epistemic justification and this is why there have been several epistemological criteria in the contemporary epistemology as additional formulations to strengthen the criteria of evaluation of statement claims, beliefs and truth in epistemology. The paper concludes that it is for this reason that such epistemic theories like contextualism, pragmatism, foundationalism, coherentism et.al have emerged as an additional force for strengthening the question and the problem of epistemic justification.  In the last section, literary works of Tunde Kelani, Ifeoma Okoye and others are x-rayed. Also, one paper in this section examines two Niger Delta plays namely: Peter Omokoâ€™s Crude Nightmen (2015) and Stephen Kekegheâ€™s Pond of Leeches (2015). It is revealed that the playwrights are unequivocal in holding indigenous leaders and citizens complicit for the systemic impoverishment of the region as a result of placing personal interests over communal progress. However, they also balance their narratives by creating parallel sets of local characters who deploy intellectual and radical forms of agency towards the liberation of their oppressed people and despoiled environment from the machinations of the enemy within. In all, this issue of KIU Journal of Humanities features many empirical and theoretical based articles. Each of them seeks to profer solutions to one social and management problem or the other. Therefore, there is something to learn by every reader of this issue.